Assessment of the suitability of Durafet-based sensors for pH measurement in dynamic estuarine environments. (5th January 2018) - Gonski, Stephen F.; Cai, Wei-Jun; Ullman, William J.; Joesoef, Andrew; Main, Christopher R.; Pettay, D. Tye; Martz, Todd R.
Abstract: The suitability of the Honeywell Durafet to the measurement of pH in productive, high-fouling, and highly-turbid estuarine environments was investigated at the confluence of the Murderkill Estuary and Delaware Bay (Delaware, USA). Three different flow configurations of the SeapHOx sensor equipped with a Honeywell Durafet and its integrated internal (Ag/AgCl reference electrode containing a 4.5 M KCl gel liquid junction) and external (solid-state chloride ion selective electrode, Cl-ISE) reference electrodes were deployed for four periods between April 2015 and September 2016. In this environment, the Honeywell Durafet proved capable of making high-resolution and high-frequency pH measurements on the total scale between pH 6.8 and 8.4. Natural pH fluctuations of >1 pH unit were routinely captured over a range of timescales. The sensor pH collected between May and August 2016 using the most refined SeapHOx configuration exhibited good agreement with multiple sets of independently measured reference pH values. When deployed in conjunction with rigorous discrete sampling and calibration schemes, the sensor pH had a root-mean squared error ranging between 0.011 and 0.036 pH units across a wide range of salinity relative to both pH T calculated from measured dissolved inorganic carbon and total alkalinity and pH NBS measured with a glass electrode corrected to pH T at in situ conditions. The present work demonstrates the viability of the Honeywell Durafet to the measurement of pH to within the weather-level precision defined by the Global Ocean Acidification Observing Network (GOA-ON, ≤ 0.02 pH units) as a part of future estuarine CO2 chemistry studies undertaken in dynamic environments. Highlights: We deployed a SeapHOx sensor package in a dynamic estuarine environment. We evaluated Durafet performance over a wide salinity range (S = 3.25 to 29.33). We evaluated Durafet performance over rapid pH fluctuations of >1 pH unit. The sensor performed well (pH RMSE = 0.011 to 0.036) relative to discrete samples. We highlighted aspects of electrode response in estuaries requiring further study.